Multifaceted approaches for data acquisition processing and communication - Chakraborty, Chinmay 1984-; Guduri, Manisha; Sandhya, B.; Shyamala, K. (CRC Press, 2024)
The objective of the conference is to bring to focus the recent technological advancements across all the stages of data analysis including acquisition, processing, and communication.
Keywords: Data Science; Datenbank; Aufsatzsammlung